Anchored PDE4 regulates chloride conductance in wild‐type and ΔF508‐CFTR human airway epithelia. Issue 2 (7th November 2013) - Blanchard, Elise; Zlock, Lorna; Lao, Anna; Mika, Delphine; Namkung, Wan; Xie, Moses; Scheitrum, Colleen; Gruenert, Dieter C.; Verkman, Alan S.; Finkbeiner, Walter E.; Conti, Marco; Richter, Wito
Abstract : Cystic fibrosis (CF) is caused by mutations in the gene encoding the cystic fibrosis transmembrane conductance regulator (CFTR) that impair its expression and/or chloride channel function. Here, we provide evidence that type 4 cyclic nucleotide phosphodiesterases (PDE4s) are critical regulators of the cAMP/PKA‐dependent activation of CFTR in primary human bronchial epithelial cells. In non‐CF cells, PDE4 inhibition increased CFTR activity under basal conditions (Δ I SC 7.1 μA/cm 2 ) and after isoproterenol stimulation (increased Δ I SC from 13.9 to 21.0 μA/cm 2 ) and slowed the return of stimulated CFTR activity to basal levels by > 3‐fold. In cells homozygous for Δ F508‐CFTR, the most common mutation found in CF, PDE4 inhibition alone produced minimal channel activation. However, PDE4 inhibition strongly amplified the effects of CFTR correctors, drugs that increase expression and membrane localization of CFTR, and/or CFTR potentiators, drugs that increase channel gating, to reach 25% of the chloride conductance observed in non‐CF cells. Biochemical studies indicate that PDE4s are anchored to CFTR and mediate a local regulation of channel function. Taken together, our results implicate PDE4 as an important determinant of CFTR activity in airway epithelia, and support the use of PDE4 inhibitors to potentiate the therapeutic benefits of CFTR correctors and potentiators.—Blanchard, E., Zlock, L., Lao, A., Mika, D., Namkung, W., Xie, M., Scheitrum, C., Gruenert, D.C., Verkman, A.S., Finkbeiner, W.E., Conti, M., Richter, W. Anchored PDE4 regulates chloride conductance in wild type and ΔF508‐CFTR human airway epithelia. FASEB J. 28, 791–801 (2014). www.fasebj.org